2010
DOI: 10.1007/s10695-009-9328-4
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and kinetic characteristics of rhodanese from the liver of African catfish Clarias gariepinus Burchell in Asejire lake

Abstract: Two forms of rhodanese were purified from the liver of Clarias gariepinus Burchell, designated catfish rhodanese I (cRHD I) and rhodanese II (cRHD II), by ion-exchange chromatography on a CM-Sepharose CL-6B column and gel filtration through a Sephadex G-75 column. The apparent molecular weight obtained for cRHD I and cRHD II was 34,500 +/- 707 and 36,800 +/- 283 Da, respectively. The subunit molecular weight determined by sodium dodecyl sulphate-polyacrylamide gel electrophoresis was 33,200 +/- 283 and 35,100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…Agboola and Okonji (2004) reported 35°C for the rhodanese in the cytosolic fraction of fruit bat liver. Also, Akinsiku et al (2010) reported 40°C for the rhodanese in the liver of catfish (C. gariepinus) from Asejire Lake, same source of tilapia for this study. Tayefi-Nasrabadi and Rahmani (2012) reported 25°C for rhodanese from the liver of rainbow trout.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Agboola and Okonji (2004) reported 35°C for the rhodanese in the cytosolic fraction of fruit bat liver. Also, Akinsiku et al (2010) reported 40°C for the rhodanese in the liver of catfish (C. gariepinus) from Asejire Lake, same source of tilapia for this study. Tayefi-Nasrabadi and Rahmani (2012) reported 25°C for rhodanese from the liver of rainbow trout.…”
Section: Discussionmentioning
confidence: 60%
“…These values are lower than those of rainbow trout (KCN = 36.81mM; Na 2 SO 4 = 19.84 mM) (Tayefi-Nasrabadi and Rahmani, 2012), african catfish liver (KCN = 25.40 mM; Na 2 SO 4 = 18.60 mM) (Akinsiku et al, 2010), fruit bat liver (KCN = 13.36 mM; Na 2 SO 4 = 19.15 mM) (Agboola and Okonji, 2004), mouse liver (KCN = 12.50 mM; Na 2 SO 4 = 8.30 mM) (Lee et al, 1995), bovine liver (KCN = 19.0 mM; Na 2 SO 4 = 6.7 mM) (Sorbo, 1953), and human liver (KCN = 9.50 mM; Na 2 SO 4 = 4.50 mM) (Jarabak and Westley, 1974), indicating that the affinity of tilapia enzyme for these substrates is more than that of the other enzymes and that it would catalyze the detoxification reaction with high efficiency. As reported by Agboola and Okonji (2004) less effective enzymatic system may be due to a lower exposure to cyanide and high affinity in some mammalian animals is due to continue exposure through their diet.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations